An Overview of Biofilm-Associated Infections and the Role of Phytochemicals and Nanomaterials in Their Control and Prevention - Tsvetozara Damyanova; Petya D. Dimitrova; Dayana Borisova; Tanya Topouzova-Hristova; Emi Haladjova; Tsvetelina Paunova-Krasteva (Pharmaceutics, 2024)
Biofilm formation is considered one of the primary virulence mechanisms in Gram-positive and Gram-negative pathogenic species, particularly those responsible for chronic infections and promoting bacterial survival within the host. In recent years, there has been a growing interest in discovering new compounds capable of inhibiting biofilm formation. This is considered a promising antivirulence strategy that could potentially overcome antibiotic resistance issues. Effective antibiofilm agents should possess distinctive properties. They should be structurally unique, enable easy entry into cells, influence quorum sensing signaling, and synergize with other antibacterial agents. Many of these properties are found in both natural systems that are isolated from plants and in synthetic systems like nanoparticles and nanocomposites. In this review, we discuss the clinical nature of biofilm-associated infections and some of the mechanisms associated with their antibiotic tolerance. We focus on the advantages and efficacy of various natural and synthetic compounds as a new therapeutic approach to control bacterial biofilms and address multidrug resistance in bacteria.